2017
DOI: 10.3390/ijms18061266
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Inducible Factor-2 Alpha and Prolinhydroxylase 2 Polymorphisms in Patients with Acute Respiratory Distress Syndrome (ARDS)

Abstract: Hypoxia-inducible-factor-2α (HIF-2α) and HIF-2 degrading prolyl-hydroxylases (PHD) are key regulators of adaptive hypoxic responses i.e., in acute respiratory distress syndrome (ARDS). Specifically, functionally active genetic variants of HIF-2α (single nucleotide polymorphism (SNP) [ch2:46441523(hg18)]) and PHD2 (C/T; SNP rs516651 and T/C; SNP rs480902) are associated with improved adaptation to hypoxia i.e., in high-altitude residents. However, little is known about these SNPs’ prevalence in Caucasians and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…This duality is perhaps best highlighted by studies that determined the prevalence of HIF2A and PHD2 polymorphisms that are associated with improved adaptation to hypoxia in high-altitude residents in patients with ARDS. This study demonstrated that the PHD2 polymorphism PHD2 RS516651-TT , which is associated with increased adaptation to high altitude, was associated with a higher 30-days mortality risk within 30 days of the onset of ARDS (Dötsch et al, 2017 ).…”
Section: Resultsmentioning
confidence: 91%
“…This duality is perhaps best highlighted by studies that determined the prevalence of HIF2A and PHD2 polymorphisms that are associated with improved adaptation to hypoxia in high-altitude residents in patients with ARDS. This study demonstrated that the PHD2 polymorphism PHD2 RS516651-TT , which is associated with increased adaptation to high altitude, was associated with a higher 30-days mortality risk within 30 days of the onset of ARDS (Dötsch et al, 2017 ).…”
Section: Resultsmentioning
confidence: 91%
“…In this context, we have previously shown that additionally to the extent of hypoxic or inflammatory stimuli or their duration, genetic variants in HIF-1, HIF-2, and HIF-degrading PHD-2 alter human adaptation to hypoxia [15][16][17][18][19]. High altitude residents thus have blunted hypoxic ventilatory response and diminished pulmonary hypertension under hypoxia [20,21], increased heart rate, improved peripheral oxygen saturation, and reduced incidence of mountain sickness, as assessed using the Lake Louise Score (LLS) [15,16,[22][23][24]. LLS, which has recently been revised, is a well-established tool to evaluate the severity of acute mountain sickness (AMS) [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Dötsch and colleagues observed that a variant of the Egl-9 family hypoxia inducible factor 1 ( EGLN1 ) gene was independently associated with greater ARDS mortality risk within 30-days in Europeans [36]. EGLN1 and the hypoxia inducible factor degrading prolyl-hydroxylases (PHD) are key regulators of the human response to a low oxygen environment, which provide a link between tissue hypoxia and the inflammatory response [46].…”
Section: Genetic Association Studiesmentioning
confidence: 99%
“…EGLN1 and the hypoxia inducible factor degrading prolyl-hydroxylases (PHD) are key regulators of the human response to a low oxygen environment, which provide a link between tissue hypoxia and the inflammatory response [46]. Despite the biological plausibility, further studies should be carried out to assess the functional impact of the genotype in EGLN1 in the mechanisms leading to ARDS [36]. Consonant to the fact that pulmonary fibrosis develops during the intermediate or late stages of ARDS, another study [37] reported the association of the strongest common risk gene variant for idiopathic pulmonary fibrosis (IPF) known to date [47] with ARDS susceptibility.…”
Section: Genetic Association Studiesmentioning
confidence: 99%